The Extra Psychiatric Psychotherapy - Valdizán, Hermilio (2014)
You know well that psychotherapy or synthetically Psychotherapy can be defined as "the cure of diseases through the spirit" as its beneficial action is the work of the established relationship between patient and physician, between subject and subject suffering that heals; between patient whose spirit craves the benefits of relief and comfort, and physician whose spirit, properly educated, understands the desires of the patient and is in a position to carry them out dutifully.